Post-Modernisme dalam Ilmu Hukum - Aeni, Nuri Qurota (Lembaga Yasin AlSys, 2022)
Post-modernism which was harnessed as a from of protest of disappointment at modernism which was considered to have failed in lifting human degrees, by using the paradigm of critical legal studies an deconstruction of thought results from Jacques derrida. This article will discuse how if postmodernisme paired with islamiclaw and how postmodernism is imolemented against lega science. The purpose of this article is to find out if Islamic law could be deconstructed as per the one offered by postmodernism. This article uses qualitative descriptive research methods. Thereas the approaches used in the article are conceptual approaches as well as legislative approarches. The data collection methods used are literature study and library research. The result of this article mentioning that Islamic law cannot be deconstructed because it is essentially hermeneutic used iin bibelic science and roman interpretation iss different from the science of the Quran.